PEMANFAATAN DAGING BUAH PALA (MYRISTICA FRAGRANS) SEBAGAI BAHAN BAKU PEMBUATAN PRODUK MINUMAN PENGHANGAT TUBUH HASIL FERMENTASI RAGI (SACCHAROMYCES CEREVISIAE) - Peren, Arnolda; Wulandhani, Suci; Zahra Al-Banna, Maisya (Universitas Cokroaminoto Palopo, 2026)
This study aims to detemine how to use of nutmeg (Myristica fragrans) as a raw material for making a body warming beverage product fermented by yeast (Saccharomyces cerevisiae), measure their alcohol content and to see the public’s interest in nutmeg fermented product. Sampling was carried out in Rubit Village Hewokloang district, Sikka regency, East Nusa Tenggara and alcohol content measurements were carried out at the Makassar health Laboratory center. Nutmeg that has been fermented by giving yeast with various treatment, namely sampel A (6 grams, sample B (10 grams) and sample C (20 grams). Fermentation was carried out for 72 hours then the alcohol content was then measured and an organoleptic test were carried out on color, teste and flavor was conducted involving 50 panelists. From the result of the organoleptic tests, the panelists preferred the fermented nutmeg drink in sample B namely with the addition of 10 grams of yeast and generally fell into the category of “fairly interesting/liked” with percentages from 41% to 60%. Meanwhile the alcohol content of each sample showed values of 6,78% for sample A, 6,99% for sample B and 7,21% for sample C. This shows that the more yeast added the higher the ethanol (alcohol) content, the longer fermentation time, then the number of microoganisms decreased.